“Efecto de diferentes dosis de fitohormonas en el cultivo de pepinillo ( cucumis sativus L.) híbrido em a american slicer 160 F1 HYB, en la provincia de Lamas” - Estrella Gamonal, Milton (2013)
The present research work entitled "effect of different doses of phytohormones in the cultivation of cucumber (cucumis sativus L.) hybrid EM American Slicer 160 F1 Hyb, in the province of Lamas", was carried out in arder to evaluate the effect of the tri and tetra hormones in the production of the cultivation of cucumber ( Cucumis Sativus L.) hibbrido, based on two different types of concentration of phytohormones, where statistical random complete blocks design was usedwith three blocks and five treatments, whose variables studied were: plant height, number of fruits produced per plant, number of harvested fruits, fruit, fruits, fruit diameter length, weight fruit yield.HA-1 (kg), fruit yield in Tn.ha-1 and economic analysis. The results obtained in this research, indicate that the applied treatments with tri hormona (Agrostemin-gl) at concentrations of 200cc.ha-1 and 400cc.ha-1, had viable and forceful responses in the variables studied in plant height (cm), performance, length and weight of the fruit, who induced physiological responses to promote growth, development of the plant, fruit formation parthenocarpic increasing the size and the weight of the fruit. The tri hormonal treatments of 200 and 400 ce. ha-1 were those who reached higher estimated returns to Ha of 104187.5 and 98058.8 fruits.ha-1. These results are products of the synergism between phytohormones (auxins, cytokinins and giberalinas) those involved directly in the physiology of the plant producing metabolic changes, osmotic and cited skeletal at the cellular leve!, giving. rise to new cells inducing growth. Key words: cucumber, hybrid variety EM American Slicer 160 F1 Hyb, phytohormones, agro-bioclimatic conditions, fruits and kg.ha-1 performance.